COMPARISON BETWEEN JOB STRESS PREDICTORS BASED ON PHYSICAL ACTIVITY, AGE, GENDER AND SENIORITY IN A GROUP OF ADMINISTRATIVE OFFICERS FROM THE COSTA RICAN PUBLIC SECTOR - Azofeifa Mora, Christian Alberto (2016)
The purpose of this article is to relate and compare job stress predictors with physical activity levels, age, seniority, and gender in administrative employees in the Costa Rican public sector. A total of 395 individuals from this sector were surveyed. Subjects answered a socio-demographic questionnaire (age, gender, seniority, and marital status). In order to assess job stress predictors, the Job Stress Survey (JSS) was applied, which was comprised of two dimensions (intensity and frequency) and including predictors such as pressure at work (PT), lack of social support (FA), lack of organization (FO), and lack of personal accomplishment (FRP). To determine the level of physical activity, a short version of the IPAQ was applied. Results indicate that male subjects have a slightly higher level of physical activity compared to female subjects. In addition, females show higher levels of job pressure as a stress predictor. Subjectively, the higher the physical activity level the lower the stressors, compared to lower levels of physical activity. We conclude that the high levels of physical inactivity exhibited may be associated with higher job stress perceived and that role overload could be an important factor to consider as a source of stress in females.